Belief persistence and reliance on traditional healing of students at central bicol state university of agriculture - Palmiano, Dariel A.; Molina, Yvette Jonathan D. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Limited scientific evidence about the safety and efficacy of traditional healing make it essential for policymakers to develop policies, regulations, and strategies to mitigate issues related to this practice. Such issues include hit-and-miss operation, incorrect diagnosis, improper dosage, low hygiene standards, and the dominant lack of statutory regulation for traditional healing practitioners and practices owing to the secrecy of some healing methods. On the other hand, the high cost of drugs and other critical considerations strengthen the belief persistence and reliance of people on traditional healing over modern medical treatments, a situation that makes it challenging for the government to define the policymaking parameters in this area. The focus of this descriptive-comparative study was to determine how persistent are the beliefs and reliance on traditional healing of students by obtaining quantitative results from a survey. A total of 277 students were surveyed using stratified proportionate random sampling. Data were gathered through a questionnaire and unstructured interviews. Descriptive statistics, dependent t-test, and one-way analysis of variance were the statistical tools used. Results showed that almost all respondents still manifest very strong belief persistence in faith healers (arbolaryo) and bone setters (hilot) and a great majority in those who cure illness caused by spirits (surhano/ parasantigwar). The illnesses they usually consult with traditional healers were vomiting, sprain, and stomachache. Male respondents have stronger belief persistence than do their female counterparts. The belief persistence and reliance of students on traditional healing, even with the recent advances in science, technology, and innovation, as well as the upsurge of new interventions for diagnosis, prevention, and treatments, indicate that the popularity of traditional healing is not declining. These findings are particularly evident in some prevailing traditional healing practices.